Loss of E-cadherin as Part of a Migratory Phenotype in Melanoma Is Associated With Ulceration. (September 2017) - Bønnelykke-Behrndtz, Marie L.; Steiniche, Torben; Nørgaard, Peter; Danielsen, Allan V.; Damsgaard, Tine E.; Christensen, Ib J.; Bastholt, Lars; Møller, Holger J.; Schmidt, Henrik
Abstract : Abstract: It has been suggested that embryogenic properties of migratory cells are reactivated during wound healing and metastasis in adults. This might explain the association between wound-induced inflammation and poor survival in patients with ulcerated melanoma. Linking inflammation with a migratory phenotype, we characterize the infiltration of innate inflammatory cells, loss of cell-to-cell adhesion (E-cadherin), factors associated with extracellular matrix degradation [matrix metalloproteinase-9 (MMP-9), and neutrophil elastase (NE)], and spindle-shaped cell morphology, between ulcerated (n = 179) and nonulcerated (n = 206) melanoma. In addition, the presence of "extravascular migratory metastasis" (angiotropism) and tumor-vessel density were evaluated as important factors for tumor cell dispersal in ulcerated melanoma. We showed a correlation between expression of the granulocyte marker cd66b+ and the expression of NE and MMP-9, reflecting activated neutrophils. Ulcerated melanoma correlated with a low global E-cadherin score ( P = 0.041) and weak-spot score ( P = 0.0004). Thus, 28% of the nonulcerated, 42% of the minimally/moderately ulcerated melanoma, and 53% of the excessively ulcerated melanoma presented low scores as opposed to a high E-cadherin score. In addition, the presence of ulceration was correlated with angiotropism ( P < 0.0001) and spindle-shaped morphology ( P = 0.021). There were no differences in MMP-9 expression or intratumoral vessel density between the ulcerated and nonulcerated group. In conclusion, expression of migratory cell properties showed a highly heterogeneous pattern, which was associated with ulcerated areas and inflammatory cells, in general and with neutrophils in particular. We, therefore, suggest that wound-associated inflammation may be involved in the induction of migratory cell transition and tumor cell dispersal in ulcerated melanoma.